Life and Career Skills in Mathematics Learning for High School Students in Indonesia: The Perspectives of Teachers and Students - Ramdani Miftah; Lia Kurniawati; Tatang Herman; Dadang Juandi; Aya Shofia Maulida (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2022)
Students need to possess the right life and career skills to face future life challenges. Therefore, this study aims to determine the effect of the life skills of mathematics teachers on high school students in Indonesia. Data were collected from 190 mathematics teachers and 627 high school students through questionnaires consisting of 15 and 45 statements for both parties. The data collected were analyzed using the Structural Equation Modeling (SEM) method and the Smart-PLS v.3.2.9 software. The results showed that the understanding of mathematics teachers (77.50%) and high school students (83%) concerning life and career skills is in a good category. Meanwhile, their life skills are in a low category due to teachers’ difficulties in translating life and career skills in planning and implementing mathematics learning. This means that the mathematics learning methods developed by teachers do not explore students' potential. Moreover, teachers’ life skills did not significantly affect each student's indicator. Only two indicators had a medium effect, namely responsibility and flexibility on leadership as well asadaptability and flexibility on initiative and self-direction